2004
DOI: 10.2486/indhealth.42.260
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Evaluation of the Chinese (Mainland) Version of Job Content Questionnaire: A Study in University Hospitals.

Abstract: To evaluate the psychometric properties of the Chinese (mainland) version of Job Content Questionnaire (JCQ), this validation study was conducted in university hospitals among 193 men and 581 women health care workers. The Cronbach's alpha coefficients for decision latitude, psychological job demands and social support ranged from 0.56 to 0.82, which indicated that psychological job demands had lower internal consistency. The decision latitude displayed a negative correlation with psychological job demands and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
105
8
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(132 citation statements)
references
References 30 publications
18
105
8
1
Order By: Relevance
“…The JCQ results in our physician sample were much higher than those of many other Taiwanese employees or the national survey means, and similar to the findings of previous cross-occupational studies 17,32) . The mean work demands and job control scores among our physician sample in Taiwan are comparable to the results of surveys of physicians in other countries 15,16) , located in the upper-right quadrant of Fig. 1.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The JCQ results in our physician sample were much higher than those of many other Taiwanese employees or the national survey means, and similar to the findings of previous cross-occupational studies 17,32) . The mean work demands and job control scores among our physician sample in Taiwan are comparable to the results of surveys of physicians in other countries 15,16) , located in the upper-right quadrant of Fig. 1.…”
Section: Discussionsupporting
confidence: 67%
“…It has been shown there was a significant difference in the job control degree between genders in our national sample 21) . In another study for a sample of hospital-based Chinese physicians, job control was significantly higher among men, and it was related to their physical health 15) . The result of our study demonstrated that the effect of job control may also be different between genders among physicians relating to their mental health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…job demand, decision latitude, social support, physical environment and personal risk factors. Psychosocial factors were measured using a questionnaire taken from the Job Content Questionnaire (JCQ) [28], [29].…”
Section: B Instrumentsmentioning
confidence: 99%